1465. A Randomized Double-Blinded Placebo-Controlled Study to Determine Efficacy of Immunoglobulin Therapy to Treat BK Viremia in Renal Transplant Recipients. (15th December 2022) - He, Kevin D; Davis, Caitlin; Ahn, Jenny; Gilligan, Hannah M; Tan, C
Abstract: Background: BK viremia in renal transplant recipients increases risk of BK virus-associated nephropathy (BKVAN), posing a threat to allograft function. Up to 30% of all renal transplant recipients develop BK viremia and 1-10% will develop BKVAN. With no effective antiviral, the mainstay of therapy to prevent BKVAN is immunosuppression reduction (IR). Case series showed potential efficacy of using intravenous immunoglobulins (IVIG) to treat BK viremia. However, a randomized placebo-controlled study is needed. Methods: A multicenter prospective double-blinded randomized placebo-controlled proof-of-concept study was conducted at three transplant institutions. 14 adult renal transplant recipients diagnosed with BK viremia were randomized (1:1) to receive IVIG and IR versus placebo and IR and were followed for 12 months, with the primary endpoint defined as resolution of BK viremia by month 3. Samples were collected at 1, 2, 3, 6, and 12 months for viral load quantification and immunological assays. Results: At enrollment, clinical characteristics of the IVIG group (n = 5) were similar to the control group (n = 9), except that a larger number of participants in the control group had delayed graft function (0% vs. 77.8%, p = 0.02) and a higher baseline BK viral load (11300 vs 99300 copies/mL, p = 0.04). At 3 months, 2 out of 5 patients in the treatment group and 4 out of 9 patients in the control group cleared their viremia (40% vs 44.4%, RR 0.89, 95% CI 0.21 – 3.35, p > 0.99). Patients who received IVIG and IR had reduction in viral load at 6 months only (11300 vs 141 copies/mL, p = 0.008). Those who received IR alone had continued reduction in viral load starting at 2 months (99300 vs 4700, 1542, 906, 278 copies/mL; p < 0.05). No participant progressed to BKVAN. Immunological profiles of each participant will be correlated to the viral load. Serum BK viral loads were higher in the placebo group than the IVIG group at enrollment, but not significantly different between the two groups at any of the follow-up time points. The dotted line represents threshold of viremia clearance at less than 1000 copies/mL. * p = 0.04. Bar – median (Mann-Whitney between group comparisons). Median serum BK viral loads of the IVIG group decreased at the 6 months follow-up time point. The dotted line represents threshold of viremia clearance at less than 1000 copies/mL. ** p = 0.008 (Mann-Whitney comparing enrollment to each follow-up time point). Median serum BK viral loads of the placebo group continued to decrease at each follow-up time point. The dotted line represents threshold of viremia clearance at less than 1000 copies/mL. * p = 0.04; ** p = 0.006; *** p = 0.0008, 0.0003 (Mann-Whitney comparing enrollment to each follow-up time point). Conclusion: This proof-of-concept study illustrates that a clinical trial of IVIG versus placebo for the treatment of BK viremia in renal transplant recipients is feasible. IVIG may not be more effective than IR alone; its immunosuppressive effect may even limit BK clearance. A larger sample is needed to attenuate baseline differences between groups and to provide a higher level of evidence on IVIG therapy in BK viremia. Disclosures: All Authors : No reported disclosures.